Advanced Techniques in Bone Regeneration - Rozim Zorzi, Alessandro; Batista de Miranda, Joao (IntechOpen, 2016)
Advanced Techniques in Bone Regeneration is a book that brings together over 15 chapters, written by leading practitioners and researchers, of the latest advances in the area, including surgical techniques, new discoveries, and promising methods involving biomaterials and tissue engineering. This book is intended for all who work in the treatment of disorders involving problems with the regeneration of bone tissue, are doctors or dentists, as well as are researchers and teachers involved in this exciting field of scientific knowledge.